Chiral Functionalization of a Zirconium Metal-Organic Framework (DUT-67) as a Heterogeneous Catalyst in Asymmetric Michael Addition Reaction - Nguyen, Khoa D.; Kutzscher, Christel; Drache, Franziska; Senkovska, Irena; Kaskel, Stefan (Inorganic Chemistry, 2018)
DUT-67, an 8-connected zirconium and 2,5-thiophenedicarboxylate-based metal-organic framework (MOF), was postsynthetically functionalized by l-proline via solvent-assisted linker incorporation to obtain a chiral base catalyst. The parent monocarboxylate could be almost completely exchanged by l-proline after 5 days of treatment. The resulting chiral DUT-67 was demonstrated to be a promising heterogeneous catalyst for the asymmetric Michael addition of cyclohexanone to trans-β-nitrostyrene with excellent yield (up to 96%) and enantioselectivity comparable to that of l-proline in homogeneous reaction (ee of approximately 38%). The Zr-MOF could be reused at least five times without substantial degradation in the crystallinity or catalytic activity. No leaching of catalytically active species into the liquid phase was detected over five cycles.
CRIS-Team Scopus Importer:2022-04-14